The relationship of self-concept and academic achievement with other variables among college preparatory and vocational course seniors in a public high school - Blanco, Virgie Concepcion F. 1951-
This study determined any significant differences between the college preparatory and vocational samples with regards to self-concept, mental ability, socio-economic status, father's level of occupation and academic achievement. This also aims to discover the relationship among the following variables: self concept, mental ability, socio-economic status, father's level of occupation and academic achievement. The study further examines which among the variables under study contribute most to academic achievement as well as self-concept.